2011
DOI: 10.1007/s00404-011-1997-4
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant FSH versus clomiphene citrate for ovarian stimulation in couples with unexplained infertility and male subfertility undergoing intrauterine insemination: a randomized trial

Abstract: Recombinant FSH is superior to CC for enabling multifollicular development in OS/IUI cycles of unexplained and male subfertile couples. Although this finding did not lead to a statistically significant superiority of rFSH in terms of clinical outcomes, the presence of relative increase by 62.5% in OPR with rFSH may be regarded as a clinically significant trend.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
52
1
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(56 citation statements)
references
References 14 publications
2
52
1
1
Order By: Relevance
“…It has been shown in many studies in the literature that the use of FSH and hMG is superior to CC use (24)(25)(26)(27). Although we observed that gestational rates were low in the CC group, we could not show the difference due to the small sample size.…”
Section: Discussioncontrasting
confidence: 87%
“…It has been shown in many studies in the literature that the use of FSH and hMG is superior to CC use (24)(25)(26)(27). Although we observed that gestational rates were low in the CC group, we could not show the difference due to the small sample size.…”
Section: Discussioncontrasting
confidence: 87%
“…First, an increasingly compelling case (Table 2) can be made in support of low-dose (%75 IU) GT regimens, for which per-cycle pregnancy rates of 8.7%-16.3% and absent highorder gestation have been noted in prospective randomized trials (28,(59)(60)(61)(62)(63)(64). A more mixed record was noted for the twin gestation category.…”
Section: Ovarian Stimulation With Iui: Is the Plurality Of Births Mitmentioning
confidence: 95%
“…It is important to reflect on the differences between these regimes. [24,25]. Clomiphene an anti-oestrogen is a selective oestrogen receptor modulator (SERM), a nonsteroidal oestrogen that binds to the oestrogen receptors at multiple sites throughout the reproductive tract and can act as an oestrogen agonist or as an antagonist.…”
Section: Discussionmentioning
confidence: 99%